2008
DOI: 10.1136/hrt.2007.121640
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels and expression of S100A8/A9 complex in infiltrated neutrophils in atherosclerotic plaque of unstable angina

Abstract: The S100A8/A9 complex may be involved in the inflammatory process of coronary atherosclerotic plaques in patients with UA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 26 publications
8
46
1
3
Order By: Relevance
“…18 In acute coronary syndrome, S100A8/S100A9 was found to be markedly expressed at the site of coronary occlusion by invading phagocytes. 19 In the present study, we extend these findings by showing increased expression of S100A8/S100A9 within carotid plaques from those patients with the most recent symptoms. Although there are several studies that Figure 1.…”
Section: Discussionsupporting
confidence: 70%
“…18 In acute coronary syndrome, S100A8/S100A9 was found to be markedly expressed at the site of coronary occlusion by invading phagocytes. 19 In the present study, we extend these findings by showing increased expression of S100A8/S100A9 within carotid plaques from those patients with the most recent symptoms. Although there are several studies that Figure 1.…”
Section: Discussionsupporting
confidence: 70%
“…This observation coupled with the positive correlation between IL-8 and Mrp-8, -14, -8/14 plaque levels might suggest a possible role for neutrophils in plaque associated inflammation. A recent study 34 demonstrated that the infiltrated neutrophils within atherectomy specimens of patients with unstable angina were Mrp-8/14 -positive. Although the focus of the present study was on the Mrp-subset of nonfoam plaque macrophages, it does not exclude the importance of other possible Mrp-cellular sources within plaque (eg, the neutrophils).…”
Section: Ionita Et Al Mrp-14 In Atherosclerotic Plaque 1223mentioning
confidence: 99%
“…Recent clinical studies have demonstrated elevated serum levels of the S100A8/A9 complex in inflammatory disorders, such as rheumatoid arthritis, 3 transplant rejection, 4 unstable angina pectoris (UAP), 5 acute myocardial infarction (AMI), 6,7 and recent MI. 8 Overexpression of the S100A8/A9 complex has been shown immunohistochemically in atherosclerotic plaques in coronary and carotid arteries.…”
Section: Editorial P 626mentioning
confidence: 99%